Challenges and opportunities in the management of metastatic renal cell carcinoma: combination therapy and the role of cytoreductive surgery. Issue 3 (May 2020) - Patel, Hiren V.; Shinder, Brian; Srinivasan, Ramaprasad; Singer, Eric A.
Abstract : Purpose of review: As the biology of metastatic renal cell carcinoma (mRCC) continues to be elucidated, novel treatments focused around immunotherapies and targeted therapies will continue to emerge. In this review, we will highlight recent treatment advances and their implications for surgical and systemic therapy. Recent findings: Several new treatments, including the tyrosine kinase inhibitor cabozantinib, the combination of a programmed cell death protein 1 antibody (nivolumab) with a cytotoxic T-lymphocyte-associated antigen 4 antibody (ipilimumab), and the combination of axitinib with pembrolizumab or avelumab have been approved by the US Food and Drug Administration as first-line therapy for the treatment of mRCC. Although promising survival benefits have been seen with these new therapies, careful patient selection is still critical. Summary: The introduction of novel therapies and the investigation of combinatorial therapies have shifted the treatment paradigm for advanced RCC. Present trials have provided promising data that could lead to further therapeutic advances.